Effect of light on the metabolism of the foraminifera Cribroelphidium selseyense lacking photosymbionts and kleptoplasts - Michael Lintner; Michael Schagerl; Bianca Lintner; Wolfgang Wanek; Nina Keul; Petra Heinz (Journal of Photochemistry and Photobiology, 2022)
Foraminifera are essential contributors to the marine carbon and nitrogen cycle. A small group of foraminifera hosts symbiotic microalgae and kleptoplasts and irradiance is a key variable influencing their metabolism. However, the majority of foraminifera is fully heterotrophic, and whether irradiance influences food ingestion patterns has remained an open question. We studied the food uptake of fully heterotrophic Cribroelphidium selseyense specimens exposed to varying light-dark cycles. Specimens obtained from the Baltic Sea were fed with lyophilised, isotopically labelled diatoms from the species of Phaeodactylum triconutum, to estimate the rate of food ingestion. We exposed the specimens to different light-dark cycles (0:24, 8:16, 16:8, 24:0 = light: dark) and irradiance intensities (0, 50, 100 and 200 µmol photons m−2 s−1) in this experiment. Differences in light-dark regime did not affect the food uptake rates of C. selseyense. Irradiance intensity, however, strongly affected food uptake, increasing with incubation time from day 1 to day 15. In parallel, the food uptake decreased with higher irradiance intensity. Therefore, we can conclude irradiance intensity and not the light-dark cycle affected food uptake of fully heterotrophic C. selseyense, leaving the mechanisms of how light intensity regulates food intake being unresolved yet.